Nice natives and mean migrants: the evolution of dispersal-dependent social behaviour in viscous populations. - El Mouden, C; Gardner, A (2008)
There has been much interest in the evolution of social behaviour in viscous populations. While low dispersal increases the relatedness of neighbours, which tends to promote the evolution of indiscriminate helping behaviour, it can also increase competition between neighbours, which tends to inhibit the evolution of helping and may even favour harming behaviour. In the simplest scenario, these two effects exactly cancel, so that dispersal rate has no impact on the evolution of helping or harming. Here, we show that dispersal rate does matter when individuals can adjust their social behaviour conditional on whether they have dispersed or whether they have remained close to their place of origin. We find that nondispersing individuals are weakly favoured to indiscriminately help their neighbours, whereas dispersing individuals are more readily favoured to indiscriminately harm their neighbours.